Effect of integrating postpartum family planning into the health extension program in Ethiopia on postpartum adoption of modern contraception - Deborah Sitrin; Gebi H Jima; Anne Pfitzer; China Wondimu; Tigist Worku Belete; Tsigue Pleah; Berhane Assefa; Tenaye Kebede; Efrem Regassa; Ezedin Aman Usman; Saifuddin Ahmed (Journal of Global Health Reports)
# Background